Songs of the Gurus : from Nanak to Gobind Singh - Khushwant Singh; Aparna Caur (New Delhi : Viking in association with Ravi Dayal, 2008)
Selections chiefly from Adi-Granth, Sikh canon
Keywords: Adi-Granth -- Translations into English; Sikhism; Sikh hymns, English; Sikh gurus; Dasam Granth -- Translations into English; Vairagmayi Bani -- Translations into English; Sikhism -- Sacred books; Guru Granth Sahib -- Translations into English; Sikhism -- Public worship -- Hymns